Edinburgh's unruly women - McNulty, Claire, author.
1 online resource (x, 173 pages)
Keywords: "Edinburgh's Unruly Women examines experiences of church discipline across parish communities through Edinburgh and its environs. The book argues that experiences of discipline were not universal, varying according to any number of factors such as age, gender, marital status, and social rank. By placing female parishioners at the heart of the book, filled with individual case studies, Edinburgh's Unruly Women appeals to students and scholars of early modern women, religion, and gender more broadly, and to those with more specialist interest in both ecclesiastical discipline and the history of early modern Scotland in the localities"--